Utilization of Waste Corncobs as Mushroom Cultivication Media in The Pataan Village, Lamongan District - M Nilzam Aly; Marlin Pernilawati Susilawati Ruyawari (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: Waste is part of environmental problems because the increase in volume of waste correlates with population growth and efforts to reduce waste are still limited. Pataan Village which is one of the villages in Sambeng Subdistrict is also inseparable from the garbage problem. Most of the household waste will be collected in the yard and then burned, both organic and inorganic waste. In Pataan Village, there is already a 3R Waste Disposal Site (TPS) which functions as a place to collect garbage and a place to sort waste, unfortunately it is not functioned optimally due to various obstacles. Purpose: Solve the problem of managing organic waste especially corncobs by maximizing it as a mushroom planting media. Method: Socialization, training and assistance of mushroom cultivation using corncobs media to youth groups who are members of the Karang Taruna Organizations in Pataan Village. Results: The results of training and assistance for 25 days, it can be noted that the optimization of corncobs as a medium for mushroom cultivation can be an effective solution in handling the waste problem in Pataan Village and has the potential to bring up new commodities in Pataan Village in the form of janggel mushrooms. Conclusion:Partners get increased knowledge and skills in utilizing corncobs as a medium for cultivating janggel mushrooms. So that in the next period can be given about how the processing of the janggel mushroom in order to have added value.